Some merry-go-round music - "Stolz, Mary, 1920-2006." (New York)
"Too complacent to quit a job she doesn't like or to refuse a date with a boy she only feels sorry for, a nineteen-year-old girl finally takes her brother's advice and begins to develop character when she declines a marriage proposal."